Reducing sedentary behaviour and promoting physical activity in children aged 7-9 years: developing, feasibility and pilot testing a low-cost, multicomponent, school- and home-based intervention. - Nally, Sarah (Ulster University, 2024)
Many primary school children in Northern Ireland (NI) are insufficiently active and spend long periods sitting. Cost-effective interventions, which increase childhood physical activity (PA) and reduce sedentary behaviour (SB) are needed to prevent future ill-health. Primary schools are a key setting for child activity promotion, yet few school-based interventions have been effective. Using a mixed-methods approach the aim of this PhD was to determine influences and approaches to reduce SB and promote PA in children aged 7-9 years, leading to the development, pilot testing and evaluation of a multicomponent primary school- and home-based intervention. A systematic review of the literature examined the effectiveness of school-based interventions at changing obesity-related behaviours in primary school children. Meta-analyses of the included interventions (n = 37) demonstrated that interventions in children when compared to controls resulted in a small positive treatment effect in moderate-to-vigorous physical activity (MVPA) in the control group (2.14; 95% CI = 0.77, 3.50). However, inconclusive results were found for SB, energy intake, and fruit and vegetable intake, and BMI kg/m2. A formative qualitative exploration involved write and draw tasks (n = 50) and semi-structured focus groups (n = 10) to examine the current views, barriers, facilitators, experiences, and perceptions of children in relation to PA in the classroom, school, and home environments, and to assess the acceptability of components for a school-based intervention. Peers and family were main influences on children's PA and could both facilitate and impede on PA participation. Collectively these findings highlight that elements of fun, social support, time, and space are likely to be central to the adaptation and maintenance of PA among primary-school children and that PA promotion strategies that are based around co-participation with peers and family members could be an effective means of engaging in PA. The findings emphasised social opportunities for PA may be effective activity promotion methods to provide the intrinsic enjoyment of PA that was expressed by these primary-school children. Semi-structured telephone interviews (n = 12) were conducted to explore current views, barriers, facilitators, knowledge, and perceptions of children’s PA and SB, both at school and within the home environment, from the perspective of their parents and classroom teachers. Results highlighted several important factors that should be closely considered when designing future PA and SB interventions, including incorporating an element of choice, adaptability, and flexibility in the intervention. Through series of iterative work, key intervention strategies were adapted from the Transform-Us! intervention to develop a context-specific school- and home-based intervention called the Children – Sit Less, Move More (C-SLAMM) intervention. A pilot cluster-randomised controlled trial (cRCT) evaluated the feasibility and effectiveness of the 8-week multicomponent school- and home-based C-SLAMM intervention, deriving estimates of the effects of the intervention on childrens’ sitting time and PA outcomes between intervention and control groups. The C-SLAMM intervention was the first multicomponent school-and home-based intervention to be undertaken in primary school children (aged 7-9 years) in NI. Primary school children were randomised by school (cluster) to participate in an 8-week intervention that used innovative behavioural, pedagogical, and environmental strategies within the classroom, school, and home settings to get participants moving more and sitting less (the C-SLAMM intervention (n = 85, four schools) or to continue with their usual PA (n = 77, four schools). Changes in time spent sitting and standing between baseline (T0) and follow-up (week 8) (T1) were assessed using an activPAL monitor (PAL Technologies, Glasgow, UK). At baseline, children in both arms (n = 76) spent 8 hours on average in sedentary pursuits (479.04 ± 82.69 minutes) and over 6 hours of sitting (363.31 ± 73.38 minutes) per day. There was no observed effect of the intervention on the primary outcome (overall sitting time) between the intervention and control schools between baseline and at follow-up (week 8). High levels of PA observed in the control group and low compliance in activPAL wear time were limitations of the study. Evaluation of the C-SLAMM intervention highlighted the importance of stakeholder buy-in from teachers, parents and pupils if school-based health promotion programmes are to be successful. This is the first known series of studies to systematically adapt the successful Transform-Us! intervention to target PA and SB in NI primary schoolchildren (aged 7-9 years). Thus, this thesis contributes to the understanding of feasible and acceptable PA and SB strategies in the school- and home- setting.
PUBLISHED
Keywords: physical activity; sedentary behaviour; Randomised Control Trial; Child Health; Schools; Health Promotion; Digital Engagement; Inclusive Society; Smart & Sustainable Planet; Behavioural Change; CHILD; Childhood obesity; Health attitudes and behaviour; Health outcomes; PHYSICAL ACTIVITY; Public health; Attitudes; Children; Health; Sports